PTH-075 The effect of storage conditions on the stability of faecal calprotectin. (22nd June 2015) - Whitehead, S; Brookes, M; French, J; Ford, C; Gama, R
Abstract : Introduction: Faecal calprotectin (f-Cp) is a sensitive non-invasive marker of intestinal inflammation used to help distinguish between inflammatory bowel disease (IBD) and functional bowel disorders such as IBS, thereby reducing the number of unnecessary endoscopic and radiological investigations in patients presenting with chronic diarrhoea. It has previously been reported that calprotectin is stable in faeces for up to seven days at room temperature (RT). A nationwide study was undertaken via the UK NEQAS Faecal Markers of Inflammation external quality assessment (EQA) programme in order to further investigate the stability of f-Cp. Method: Complete 24 h stool collections were provided by three IBD patients. Each stool was homogenised and split into six portions, each of which was stored under different conditions: i) RT (∼20˚C) for seven days; ii) RT for 14 days; 4°C for seven days; 4°C for 14 days and; two portions immediately frozen at –40°C. Following storage, the portions not already in the freezer were frozen at –40°C. Sub-aliquots of each of the six portions from each patient were dispatched to the participants of the UK NEQAS Faecal Markers of Inflammation EQA scheme for analysis. Results: Forty-four scheme participants returned results. Mean f-Cp concentrations in the baseline specimens were 9.3–95.4 µg/g [patient 1], 204–449 µg/g [patient 2] and 5.5–66.4 µg/g [patient 3]. F-Cp levels decreased over the period of 14 days when the stool samples were stored at RT but to varying degrees depending upon the initial concentration and the assay used for analysis. For the most severely-affected method (Thermo Fisher ELiA) f-Cp levels decreased by ∼50% following storage at RT for 14 days in the specimen from patient 2. No decrease was observed for the same assay at lower f-Cp concentrations [patients 1 and 3] under the same conditions. No effect of storage was observed at either RT or 4°C for the users of the Buhlmann, Immundiagnostik, Calpro (ELISA) and Buhlmann Quantum Blue assays at lower f-Cp concentrations [Patients 1 and 3]. Storage for 14 days at 4°C had no significant effect for the Buhlmann ELISA, Calpro ELISA and Quantum Blue users at higher f-Cp concentrations (Patient 2). A decrease of ∼10% was observed for the Thermo Fisher ELiA and Immundiagnostik ELISA assays stored under the same conditions. Conclusion: The conditions under which stool samples are transported and stored prior to calprotectin analysis can affect the results obtained in the laboratory depending upon the baseline f-Cp level and the particular assay being used for analysis. Our data also further highlights the between-assay variability that exists amongst f-Cp kits. Disclosure of interest: None Declared.